The moral dimension of asymmetrical warfare counter-terrorism, democratic values and military ethics - Baarda, Th.A. van; Verweij, D.E.M (Martinus Nijhoff, 2009)
During the Cold War - an era in which the term 'asymmetric warfare' was not well known - the issue of the laws and ethics of war seemed simple enough to most soldiers, being concerned mainly with leadership, management, and morale. Post-Cold War reality revealed a very different set of challenges, including a significantly wider moral dimension, particularly when forces, initially under UN leadership and later under the NATO flag, were deployed in different parts of the turbulent Balkans. Military observers, by now with legal advisers close by, watched events in the Balkans, East Timor and then in central and West Africa with professional interest, and some were involved there. Soldiers were subsequently caught as much by surprise by the events of 9/11, and a graphic example of asymmetric warfare, as most of the rest of the world.The initial, post 9/11 response in Afghanistan brought the notion of the fragile or collapsed state, and the blurring of the roles of military forces, international organisations, non-government organisations, non-state actors, and indigenous administrators and their uniformed organisations, and with them the moral dilemmas, to much wider notice. More recent conflicts have indeed shown the need for commanders and soldiers in all types of conflict to have a much better understanding of the complex moral and legal environments, and opened new debates about the principle of 'winning hearts and minds' in counter-insurgency and peace support operations. Technology has also produced mixed benefits in the field of military operations, and posed additional dilemmas, many of them moral: remotely piloted vehicles, some of them carrying missiles, non-lethal weapons, surveillance and search equipment, as well as networked capability, and all pose questions about their use on the battlefield.The trend towards defining human rights and 'fundamental freedoms' poses further questions for the soldier today. This collection of essays, written by a wide variety of practising experts and scholars, touches on all these issues. It links the medieval traditions of jus in bello, codified by Saint Thomas Aquinas in the Christian Church nearly eight centuries ago, to examination of modern challenges and moral dilemmas relating to the ethics and laws of conflict and crises of all types in the twenty-first century, and in a global context among people of many different faiths and beliefs, and none. It is an important collection for all those researching or practically involved in conflict and post-conflict situations: few people entering an operational area or 'battlespace' in the twenty-first century will have to wait for long before being confronted with the complex and difficult situations on which the challenging discussions in this book shed light.